Relationship between body weight, body measurements and carcass characteristics of Nile tilapia (Oreochromis niloticus L.) - Portillo-Salgado Rodrigo; Sánchez-Márquez Alondra Y.; Oney-Montalvo Julio E.; Dzib Cauich Dany A.; Chi-Gutiérrez Emmanuel De Jesús (Biotechnology in Animal Husbandry)
This study was conducted to evaluate the relationship between the body weight (BW), body measurements and carcass characteristics to determine the usefulness of body measurements in prediction of BW and fillet and carcass weight of Nile tilapia (Oreochromis niloticus L.). In the study, a total of thirty-six adult male tilapia specimens were used. The fish were killed and weighed individually using an electronic scale. Six linear body measurements were recorded: total length (TOL), standard length (STL), body width (BWI), body perimeter (BPE), body height (BHE) and head length (HEL). Likewise, the fish were processed to determine the carcass weight (CWE), viscera weight (VIW), head weight (HEW), fillet weight (FIW), backbone weight (BAW) as well as carcass (CYI) and fillet (FIY) yields. The results of the study indicated that the mean values of BW, body measurements and carcass characteristics presented low to moderate variability, varying from 3.45% for TOL to 26.74% for HEW. The Pearson correlation coefficients ranged from moderate to high (0.342 ≤ r ≤ 0.869). All the linear body measurements, except HEL, showed positive correlations with BW (P<0.001). Also, BW showed positive correlations (P<0.05; P<0.001) with the CWE (r= 0.869), FIW (r= 0.638), VIW (r= 0.395) and BAW (r= 0.360). The results of the stepwise regression analysis revealed that BW can be moderately predicted using BHE and STL as the predictor's variable. Besides, BW was the traits of higher importance in the prediction of CWE (R2 = 75.6%) and FIW (R2 = 40.7%). These findings contribute to decision making related to breeding programs of this aquaculture species.